2016
DOI: 10.1007/s10883-016-9329-4
|View full text |Cite
|
Sign up to set email alerts
|

On Sub-Riemannian Geodesics in SE(3) Whose Spatial Projections do not Have Cusps

Abstract: We consider the problem P curve of minimizing L 0 ξ 2 + κ 2 (s) ds for a curve x in R 3 with fixed boundary points and directions. Here, the total length L ≥ 0 is free, s denotes the arclength parameter, κ denotes the absolute curvature of x, and ξ > 0 is constant. We lift problem P curve on R 3 to a sub-Riemannian problem P mec on SE(3)/({0} × SO (2)). Here, for admissible boundary conditions, the spatial projections of sub-Riemannian geodesics do not exhibit cusps and they solve problem P curve . We apply th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 31 publications
2
33
0
Order By: Relevance
“…Comparing the left and right figure, we note that the higher m, the higher the values for ρ where this branching occurs. Moreover, we have that Im(λ ρD 44 ) ∼ O(ρD 44 ).…”
Section: The Time-integrated Processmentioning
confidence: 80%
See 1 more Smart Citation
“…Comparing the left and right figure, we note that the higher m, the higher the values for ρ where this branching occurs. Moreover, we have that Im(λ ρD 44 ) ∼ O(ρD 44 ).…”
Section: The Time-integrated Processmentioning
confidence: 80%
“…Future work will include extensive analysis of the Monte-Carlo simulations, briefly described in Appendix E. Furthermore, we will put connections of hypo-elliptic diffusion (and Brownian bridges) on SE(3) and recently derived sub-Riemannian geodesics in SE(3) [44].…”
Section: Resultsmentioning
confidence: 99%
“…where A i are left-invariant vector fields on the group SE 3 , the controls u 3 , u 4 , u 5 are real-valued L ∞ (0, t 1 ) functions, the terminal time t 1 > 0 is free, e is the identity transformation of R 3 , g is a given element of SE 3 and ξ > 0 is a parameter that balances the influence of translation and rotations in R 3 on the length of the corresponding trajectory. Investigation of this problem was initiated in [7,12], where in particular it was shown that due to the scaling homothety, see [7,Remark 5], the general case ξ > 0 reduces to the case ξ = 1 by linear change of variables. Further in the article, we assume ξ = 1 without loss of generality.…”
Section: Introductionmentioning
confidence: 99%
“…Application of PMP to our problem gives an expression of extremal controls in terms of momenta (conjugate variables). Namely, the extremal controls u 3 , u 4 , u 5 coincide with three certain momenta, see [7,Section 3.1]. We denote the remaining three momenta by u 1 , u 2 and u 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation